PENGARUH KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT.MITRA SUARA SEJATI KUPANG - Yody A. Manafe; Rolland E. Fanggidae; Ni Putu Nursiani (Universitas Nusa Cendana, 2018)
This study used Job Satisfaction and Work Motivation as independent variable and workProductivity as dependent variavel. This research was conducted at PT. Mitra Suara Sejati Kupangwith a sample of 30 employees of PT. Mitra Sejati Sejati Kupang. Data collection usingquestionnaires, interviews, and observation techniques. The result of the research showed that (1)Job Satisfaction, Work Motivation and Work Productivity of PT.Mitra Suara Sejati Kupangemployees was in high criteria, very high, and very high. (2) Job Satisfaction and Work Motivationhad positive and significant effect to Work Productivity of employees of PT. Mitra Sejati SejatiKupang. This was shown in the Linear Regression formula: Y = 23.914 + 0.416X1+ 0.384X2.Partial test result showed ; tcount for Job Satisfaction variable = 2.333 and tcount for Work Motivationvariable = 2.156 which both larger than ttable = 1.703, so it proved that Job Satisfaction And WorkMotivation had partially affect on Work Productivity of employees.The result of hypothesis testing(F) proved that Job Satisfaction and Work Motivation had positive and significant effectsimultaneously on employee Work Productivity, viewed from Fcount (5,140) > Ftable (3,35) withDeterminant Coefficient (R2) was equal to 27,6%.Keywords: Job Satisfaction, Work Motivation, and Work Productivity